Design Thinking as an Educational Tool for Project Management Classes - Oliveira, Gustavo Pott de; Fontoura, Lisandra Manzoni (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
Design Thinking has gained wide acceptance in the software industry as an effective approach for fostering innovation and user-centered solutions. This paper presents the design and application of a classroom activity aimed at introducing Design Thinking within the context of a Software Project Management course. The activity engaged undergraduate students in Computer Science and Information Systems in the creation of educational game prototypes based on course topics, enabling them to experience each stage of the Design Thinking process. Due to time constraints in academic settings, we adapted the original method to fit within limited class sessions, resulting in a relevant outcome of this work. Through collaborative problem-solving and iterative prototyping, students explored alternative ways to approach technical content. The results indicate that the use of Design Thinking in this setting not only supported conceptual understanding and teamwork but also encouraged creativity and a stronger alignment between academic learning and industry-relevant practices.